PENGARUH DAN DAMPAK KERUSAKAN JALAN TERHADAP PENGGUNA JALAN RAYA WAMENA-TIOM KECAMATAN GOLLO KABUPATEN LANNY-JAYA PAPUA PEGUNUGAN - Dani Wenda; Shirly Susane Lumeno; Nicki Willem Rampengen (Sustainable Construction (SUSCON), 2024)
The main road in Wamena, namely the Wamena-Tiom highway on the west side, connecting to the city of Tiom and its surroundings, experiences high traffic density throughout the day. This research aims to 1) Know the road, 2) Know the effect of road damage on road users. Data collection techniques use primary data and secondary data. The data analysis technique uses descriptive quantitative analysis techniques. The research results show that the impact of road damage on the Wamena-Timo highway has an impact on safety, comfort, vehicle damage, traffic and operational costs. So it can be concluded that there must be improvements to minimize the impact of road damage.